Hydrophobic edible packaging film / Suhana Ezzureen M Suhaimi ... [et al.] - M Suhaimi, Suhana Ezzureen; Zakaria, Nurul Aimi; Alias, Ahmad Nazib; Mohamed Zabidi, Zubainun; Kamarul Ariffin, Muhammad Kamarul Thaqif; Abdul Rahim, Nur Lailatul Syafiqah; Junaid, Aiman Haiqal Faizai (2020)
Nowadays, plastic usage had increased drastically compared to 10 years ago. This is caused by the plastics are required to be used due to their various ability in as packaging in the food industry such as plastic bags, cups, spoon, plates, and bowl. This had caused the increase in the amount of plastic pollution that had occurred all around the world because the improper disposal of the plastic will lead to a huge waste because plastic generally took about 1000 years for it to fully decay. Therefore, the purpose of our project is to create an edible bio-plastic to help even at least slightly at alleviating the issue of plastic pollution since our bioplastic will be edible both to human and animal and also the plastic would biodegradable which means it would take a shorter time for it to fully decay. The bio-plastic was made with cassava mix separately with agar and gelatin to further enhance the properties of the plastic. This plastic was tested for tensile and elongations with 3:1 ration of Gelatin and Cassava being the best bio-plastic in terms of the test.